ANALISIS KINERJA SAHAM ANTM DAN INCO SERTA HARGA KOMODITAS EMAS SEBELUM DAN SESUDAH PERANG RUSIA-UKRAINA - Buntuborrong, Yunovisri Valenrio; Tumewa, Steven; Kandiawan, Emeline Aime; Maichal, Maichal (Ma Chung Press, 2025)
The Russia-Ukraine war has created uncertainty in the world economic situation, including Indonesia. This economic uncertainty has encouraged people to tend to make safe economic decisions that do not have high risks. Gold commodities are one of the main choices for people to secure their assets because the value of gold is stable even in the midst of economic uncertainty. The increase in demand for gold commodities when economic certainty occurs will affect the selling price of gold commodities and the stock performance of metal and mineral mining companies. Therefore, this study aims to determine the effect of the impact of the Russia-Ukraine war on the stock performance of metal and mineral mining companies and the price of gold commodities in Indonesia. The study was conducted quantitatively using PT Aneka Tambang Tbk (ANTM) and PT Vale Indonesia Tbk (INCO) as samples to determine the impact of the Russia-Ukraine war on the stock performance of metal and mineral mining companies in Indonesia. Gold commodities were selected as samples from the mining commodity population. The data used in this study were obtained by collecting secondary data sourced from the TradingView website and using SPSS software as an analysis tool. This study uses a different test method to determine the comparison of the performance of mining and mineral sector companies' stocks and gold commodity prices 3 months before and during the Russo-Ukrainian war. The results of the study indicate that there are significant and insignificant price differences before and during the Russo-Ukrainian war. The price difference between before and during the Russo-Ukrainian war indicates that there was an increase in prices after the peak of the Russo-Ukrainian war. This price difference indicates that the mining commodity sector was strongly affected by the war.